Development and Validation of the Mathematics Test for Tenth Grade Jordanian Students, According to the Partial Credit Model - Hani, Anwar Bani; Talib, Rohaya; Zrekat, Mutasem; Nasir, Mohd Alfouzii; Al Ahmad, Areej; Wedian, Nariman (Turkish journal of computer and mathematics education, 2021)
The study aimed at developing and validating the mathematics test for 10th –grade students according to the Rasch partial credit model (PCM) by using the descriptive approach as it is appropriate for the study aims. To achieve the study's objective, what constructed the essay type test consisted of 25 items based on the (IRT) according to the Rasch PCM. what conducted the first administration of the test to verify the validity and reliability of the test. To verify the "face validity" of the test's objectives, they were presented to a group of 12 arbitrators who work as teachers and educational supervisors. They found that the contents are representative of the level of the goal, which is pursuing in theory. The empirical reliability was calculated for the test, where the value of person reliability reached 0.91. Moreover, the items reached 0.93. The study population consisted of all 10th-grade students at the schools belonging to the “Directorate of Education of Irbid District,” whose numbers were 7365, represented by 3612 male students, and 3753 female students. According to the class regarding their sex (gender), a sample according to a cluster as the test unit was the class section. The sample size of the study was 250 male and female students. According to the PCM, this study's findings have brought several issues concerning the mathematics subject achievement by verifying the tests and reliability and accomplishing the IRT's suppositions.